The Influence of Tax Knowledge and Tax Literacy on MSME Tax Compliance - Putri, Asri Amelia; Sholaha, Alena Layla; Oktaviana, Anisa Eka; Annas, Amalia Hikmah; Afifah, Maudina Rahma (Gorontalo Accounting Journal, 2026)
This study examines how tax knowledge and tax literacy influence tax compliance among Micro, Small, and Medium Enterprises (MSMEs). A quantitative descriptive design was applied, with primary data obtained from questionnaires completed by 50 MSME owners in Bandung City, selected through purposive sampling. The collected data were processed using statistical testing procedures, including validity and reliability assessments, followed by multiple linear regression analysis. The findings reveal that tax knowledge significantly enhances MSME tax compliance, indicating that a solid understanding of tax regulations, obligations, and sanctions encourages compliant behavior. Conversely, tax literacy demonstrates a positive yet statistically insignificant relationship, suggesting that technical comprehension alone may not directly result in compliance. Therefore, strengthening tax knowledge is considered a key factor, supported by continuous government initiatives through practical and targeted tax education programs tailored to MSME characteristics.